1986
DOI: 10.1111/j.1439-0434.1986.tb04370.x
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation and Suppression of Phytoalexin and Isoflavone Accumulation in Cotyledons of Cicer arietinum L. as Caused by Wounding and by Polymeric Components from the Fungus Ascochyta rabiei

Abstract: Shortly after sowing cotyledons of chickpea (Cicer arietinum) start to accumulate the isoflavones biochanin A and formononetin together with their 7‐0‐glucosides and their 7‐0‐glucoside‐6″‐malonates. The additional accumulation of the pterocarpan phytoalexins medicarpin and maackiain can be induced by wounding of the cotyledons. Treatment of sliced cotyledons with a crude elicitor fraction obtained from the growth medium or the mycelium of the chickpea pathogenic fungus Ascochyta rabiei (Pass.) Lab. leads to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The induction of phytoalexins may be circumvented or delayed by evading recognition by the surveillance system of the host plant. There is also evidence for some plant-fungus interactions to indicate that fungi may produce molecules that suppress plant defence responses, including phytoalexin biosynthesis (Zeigler and Pontzen, 1982;Kessman and Barz, 1986;Shiriashi et al, 1992).…”
Section: Avoiding the Issuementioning
confidence: 96%
“…The induction of phytoalexins may be circumvented or delayed by evading recognition by the surveillance system of the host plant. There is also evidence for some plant-fungus interactions to indicate that fungi may produce molecules that suppress plant defence responses, including phytoalexin biosynthesis (Zeigler and Pontzen, 1982;Kessman and Barz, 1986;Shiriashi et al, 1992).…”
Section: Avoiding the Issuementioning
confidence: 96%
“…Thus, compatible bacterial pathogens may have evolved mechanisms to inhibit or suppress the induction of plant defense responses. A number of studies have indicated that funga1 pathogens produce such suppressors of plant defense responses (Doke et al, 1980;Ziegler and Pontzen, 1982;Kessmann and Barz, 1986;Yamada et al, 1989). Transposon insertion mutants of Xanthomonas campestris pathovars have been isolated that induce hypersensitive reactions on normally susceptible plants, suggesting that bac-teria1 plant pathogens might also produce suppressors (Daniels et al, 1984;Kamoun et al, 1992); however, to date, no suppressor has been isolated from a bacterial pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pathogens must overcome the host resistance induced by various elicitors to succeed in the infection , Shiraishi et al 1994. The molecules able to suppress the active resistance of host plants to such responses as hypersensitive cell death (Doke 1975, Storti et al 1988, superoxide generation (Doke 1983), and accumulation of phytoalexin (Shiraishi et al 1978, Doke et al 1979, Kessmann and Barz 1986 are called suppressors (reviewed by Shiraishi et al 1994, Shiraishi et al 1999.…”
Section: Introductionmentioning
confidence: 99%